1996
DOI: 10.1074/jbc.271.40.24954
|View full text |Cite
|
Sign up to set email alerts
|

A Thumb Subdomain Mutant of the Large Fragment of Escherichia coli DNA Polymerase I with Reduced DNA Binding Affinity, Processivity, and Frameshift Fidelity

Abstract: In Klenow fragment DNA polymerase, a flexible 50-amino acid subdomain at the tip of the thumb which includes two ␣ helices has been suggested to interact with the duplex template-primer (Beese, L.S., Derbyshire, V. and Steitz, T.A. (1993) Science 260, 352-355). The present study investigates the properties of Klenow polymerase containing a 24-amino acid deletion (residues 590 -613) that removes a portion of the tip of the thumb. The mutant polymerase has relatively normal dNTP binding and catalytic rate. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 43 publications
6
66
2
1
Order By: Relevance
“…The mutator effects observed here are distinctly different from earlier observations with mutants of HIV-1 reverse transcriptase (8,9) or Klenow fragment (10). Those enzymes are mutators for frameshifts in homopolymeric runs that may be initiated by template-primer slippage, and they contain changes in the thumb subdomain thought to interact with the duplex template-primer.…”
Section: Fig 1 Error Spectra For Klenow Polymerasescontrasting
confidence: 55%
See 1 more Smart Citation
“…The mutator effects observed here are distinctly different from earlier observations with mutants of HIV-1 reverse transcriptase (8,9) or Klenow fragment (10). Those enzymes are mutators for frameshifts in homopolymeric runs that may be initiated by template-primer slippage, and they contain changes in the thumb subdomain thought to interact with the duplex template-primer.…”
Section: Fig 1 Error Spectra For Klenow Polymerasescontrasting
confidence: 55%
“…Alanine scanning mutagenesis of helix H has identified two mutant reverse transcriptases that have strongly reduced DNA binding affinity, reduced processivity, and reduced fidelity for errors in homopolymeric runs that were consistent with the strand slippage model (8,9). More recently, we have found that a mutant derivative of Klenow fragment polymerase lacking 24 amino acids at the tip of the thumb has reduced DNA binding affinity and also has reduced fidelity for one-base addition and deletion errors in homopolymeric runs (10). These frameshift mutator mutants of HIV-1 reverse transcriptase and Klenow polymerase have relatively normal rates for base substitution errors initiated by nucleotide misinsertion.…”
mentioning
confidence: 81%
“…However, the loss of DNA binding activity occurred without significant loss of exonuclease activity. Biochemical studies suggest that 5-8 base pairs of duplex DNA are covered by E. coli Klenow fragment when the primer terminus is in the pol active site (33). In the co-crystal structure of an editing complex, the 3Ј terminus is bound in the exo active site, whereas the duplex portion of the template-primer occupies the cleft between exo and pol domains similar to binding in the pol mode (18,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although we show that our polymerase-defective mutants PKL, GWF, and W576A bind the duplex oligonucleotide substrate poorly, binding to the mismatched DNA substrate is clearly sufficient for these holoenzymes to hydrolyze efficiently a 3Ј-terminal mispaired nucleotide. The earlier study showed that the tip of the thumb subdomain in Klenow is important for template-primer DNA binding and enzyme processivity (33); side chain changes in the thumb also affect the fractional occupancies of template-primer into the two active sites (44). Likewise, amino acid substitutions in the spacer region of the catalytic subunit of pol ␥ may increase the partitioning of the 3Ј terminus to the 3Ј-5Ј exonuclease active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation